2015
DOI: 10.1098/rsif.2014.1057
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton remodelling of confluent epithelial cells cultured on porous substrates

Abstract: The impact of substrate topography on the morphological and mechanical properties of confluent MDCK-II cells cultured on porous substrates was scrutinized by means of various imaging techniques as well as atomic force microscopy comprising force volume and microrheology measurements. Regardless of the pore size, ranging from 450 to 5500 nm in diameter, cells were able to span the pores. They did not crawl into the holes or grow around the pores. Generally, we found that cells cultured on non-porous surfaces ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…Scanning an 8 × 8 μm area indicated in Figure 2A revealed microvilli with lengths of 0.8-1 μm and diameter of 80-100 nm laying across the cell surface ( Figure 2B). Even though the appearance of microvilli on life cells is not clear, an upright, brush-like spatial configuration is likely, and fixing the cells destroys this native structure (Rother et al, 2015). Live MDCK C11 cells are shown in Figure 3 in which a 100 × 100 μm area of the monolayer was imaged with a peak force of 200 pN showing no disturbances by cantilever-cell contacts even though height differences of more than 10 μm are present ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning an 8 × 8 μm area indicated in Figure 2A revealed microvilli with lengths of 0.8-1 μm and diameter of 80-100 nm laying across the cell surface ( Figure 2B). Even though the appearance of microvilli on life cells is not clear, an upright, brush-like spatial configuration is likely, and fixing the cells destroys this native structure (Rother et al, 2015). Live MDCK C11 cells are shown in Figure 3 in which a 100 × 100 μm area of the monolayer was imaged with a peak force of 200 pN showing no disturbances by cantilever-cell contacts even though height differences of more than 10 μm are present ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, Rother et al studied the morphological and viscoelastic properties of confluent MDCK-II cells grown to confluence on porous substrates with defined pore size [65]. Essentially, it was found that cells grown on large pores in the micrometer range appear softer and behave more liquid-like.…”
Section: Impact Of Substrate Topographymentioning
confidence: 96%
“…In agreement, conserved apicobasal polarization and tight junction formation were reported for MDCK on porous substrates with similar sizes. 43 Inside hexagons, cells formed long, actin-rich protrusions in D7H5 structures, covering the whole microstructures by extending down to the glass bottom from 1 day after seeding, as visualized by F-actin staining Table 1 in the supplementary material 50 ]. Most of the results described in Secs.…”
Section: B Cells Generate Basal Protrusions In Hexagonal Latticesmentioning
confidence: 99%
“…48 A work on MDCK cells on porous materials, with holes between 0.45 and 5.5 μm, showed that cells grown over pores were less stiff and more fluid than cells on nonporous substrates; however, no deep protrusions seemed to be formed, which may be due to pore depth or substrate. 43 In larger pores of 50-500 μm width, cells generated protrusions of various thickness to sense their environments, in particular, protrusions horizontally bridging wells. 30…”
Section: Engagement Of Nuclei and Intercellular Junctions In Hexagonsmentioning
confidence: 99%